The macroeconomic impacts of Chinese currency appreciation on China and the rest of world: A global computable general equilibrium analysis - Yang, Jun; Zhang, Wei; Tokgoz, Simla (International Food Policy Research Institute, 2012)
There has been contentious debate surrounding the issue of undervaluation of the Chinese Renminbi. Despite continuous international political pressure to appreciate its currency, the Chinese government has resisted significant changes. A key question underlining the debate is whether a Renminbi appreciation would deliver substantial gains for exports and employment as the United States has argued or a significant slowdown of Chinese economy as feared by the Chinese government, and if so to what extent. This paper analyzes the ex-ante, short-term impacts of the Chinese Renminbi appreciation on the Chinese and world economies using the novel approach of modeling nominal exchange rate adjustment in the Global Trade Analysis Project, a global computable general equilibrium model. Scenario results show that the Chinese economy will be affected negatively, with lower real gross domestic product, lower employment rates, and a decline in the trade surplus. Chinese currency appreciation has a positive impact on the GDP of the major countries and regions, but by a small margin. With a higher Chinese exchange rate, trade balances for other trading partner countries, with the exception of the United States, improve.